Could oral hygiene prevent cases of at-home-acquired Legionnaires’ disease? – Results of a comprehensive case–control study on infection sources, risk, and protective behaviors - Lehfeld, Ann-Sophie; Reber, Franziska; Lewandowsky, Marina M.; Jahn, Heiko J.; Lück, Christian; Petzold, Markus; Schaefer, Benedikt; Germelmann, Anna-Rachel; Lorenz, Katrin; Buchholz, Udo (Frontiers in Microbiology, 2023)
The “LeTriWa study” on community-acquired cases of Legionnaires' disease (LD) found that most cases likely acquired their infection at home (AHALD). However, which sources confer the infection is largely unknown. We therefore analyzed the data using bivariate and multivariate analyses to find out if individual sources were associated with AHALD and if specific behavioral habits increase or lower the risk for AHALD. During the study we had used two comparison groups: (i) controls matched for age group and hospital (“controls”), (ii) household members of cases with AHALD (“AHALD-HHM”). We inquired about exposure to water sources, such as showering or wearing dentures, as well as behavioral factors and habits related to oral hygiene. We took standardized household bathroom water and biofilm samples of both cases with AHALD and controls, and in addition from households of cases with AHALD only samples from suspect residential (non-)drinking water sources. There were 124 cases with AHALD, 217 controls and 59 AHALD-HHM. In bivariate analyses using controls for comparison, wearing dentures was the only variable significantly positively associated (odds ratio (OR) = 1.7, 95% confidence interval (CI) = 1.1–2.7, p-value = 0.02). Behavioral factors such as showering, letting water run before use and not being alcohol abstinent were significantly negatively associated, smoking was significantly positively associated. In a multivariable analysis, we identified good oral hygiene as a preventive factor for both denture wearers (OR = 0.33, 95% CI = 0.13–0.83, p-value = 0.02) and non-denture wearers (OR = 0.32, 95% CI = 0.10–1.04, p-value = 0.06). Analyses of comparisons with AHALD-HHM showed similar effects but lacked statistical power. We identified Legionella in 16 residential (non-)drinking water sources, one of which was a PCR-positive scratch sample of dentures. Wearing (inadequately cleaned) dentures or poor oral hygiene might confer an increased risk for AHALD, and oral hygiene may prevent AHALD. The hypothesis that Legionella in oral biofilm or dental plaque may be the cause of cases with AHALD should be examined further. If confirmed this may open new and simple avenues for the prevention of LD.